The Law of Stigma, Travel, and the Abortion-Free Island - Erdman, Joanna N. (Columbia Journal of Gender and Law, 2016)
In 1988, the Supreme Court of Canada decriminalized abortion in R. v. Morgentaler. Almost immediately thereafter, the Maritime province of Prince Edward Island (“P.E.I.”) passed a legislative resolution opposing the provision of abortion services on the Island except to save the life of a pregnant woman. P.E.I. is a small pastoral province of rolling hills and ocean coves in the St. Lawrence Gulf, and since 1988, through various regulatory actions, its government has honored this policy promise to keep the Island abortion-free and to preserve its moral landscape.